$y = \exponential{x}{2} + \fraction{\exponential{y}{2} x}{2}$

## 共享

y-x^{2}=\frac{y^{2}x}{2}

y-x^{2}-\frac{y^{2}x}{2}=0

2y-2x^{2}-y^{2}x=0

-2x^{2}-xy^{2}+2y=0

\left(-x\right)y^{2}+2y-2x^{2}=0

y=\frac{-2±\sqrt{2^{2}-4\left(-x\right)\left(-2x^{2}\right)}}{2\left(-x\right)}

y=\frac{-2±\sqrt{4-4\left(-x\right)\left(-2x^{2}\right)}}{2\left(-x\right)}

y=\frac{-2±\sqrt{4+4x\left(-2x^{2}\right)}}{2\left(-x\right)}

y=\frac{-2±\sqrt{4-8x^{3}}}{2\left(-x\right)}

y=\frac{-2±2\sqrt{1-2x^{3}}}{2\left(-x\right)}

y=\frac{-2±2\sqrt{1-2x^{3}}}{-2x}

y=\frac{2\sqrt{1-2x^{3}}-2}{-2x}

y=-\frac{\sqrt{1-2x^{3}}-1}{x}
-2+2\sqrt{1-2x^{3}} 除以 -2x。
y=\frac{-2\sqrt{1-2x^{3}}-2}{-2x}

y=\frac{\sqrt{1-2x^{3}}+1}{x}
-2-2\sqrt{1-2x^{3}} 除以 -2x。
y=-\frac{\sqrt{1-2x^{3}}-1}{x} y=\frac{\sqrt{1-2x^{3}}+1}{x}

y-\frac{y^{2}x}{2}=x^{2}

2y-y^{2}x=2x^{2}

-xy^{2}+2y=2x^{2}

\left(-x\right)y^{2}+2y=2x^{2}

\frac{\left(-x\right)y^{2}+2y}{-x}=\frac{2x^{2}}{-x}

y^{2}+\frac{2}{-x}y=\frac{2x^{2}}{-x}

y^{2}+\left(-\frac{2}{x}\right)y=\frac{2x^{2}}{-x}
2 除以 -x。
y^{2}+\left(-\frac{2}{x}\right)y=-2x
2x^{2} 除以 -x。
y^{2}+\left(-\frac{2}{x}\right)y+\left(-\frac{1}{x}\right)^{2}=-2x+\left(-\frac{1}{x}\right)^{2}

y^{2}+\left(-\frac{2}{x}\right)y+\frac{1}{x^{2}}=-2x+\frac{1}{x^{2}}

\left(y-\frac{1}{x}\right)^{2}=-2x+\frac{1}{x^{2}}

\sqrt{\left(y-\frac{1}{x}\right)^{2}}=\sqrt{-2x+\frac{1}{x^{2}}}

y-\frac{1}{x}=\frac{\sqrt{1-2x^{3}}}{|x|} y-\frac{1}{x}=-\frac{\sqrt{1-2x^{3}}}{|x|}

y=\frac{\sqrt{1-2x^{3}}}{|x|}+\frac{1}{x} y=-\frac{\sqrt{1-2x^{3}}}{|x|}+\frac{1}{x}